Fostering Inquiry and Creativity in Early Years STEM Education: Policy Recommendations from the Creative Little Scientists Project - Stylianidou, Fani; Glauert, Esme; Rossis, Dimitris; Compton, Ashley; Cremin, Teresa; Craft, Anna; Havu-Nuutinen, Sari (European journal of STEM education, 2018)
"Creative Little Scientists" was a 30-month (2011-2014) EU/FP7-funded research project focusing on the synergies between early years science and mathematics education and the development of children's creativity, in response to increasing interest in these areas in European educational policy. Using a variety of methods, including desk research, a teacher survey and classroom-based fieldwork, the research provided insights into whether and how children's creativity is fostered and appropriate learning outcomes, including children's interest, emerge. Based on these and ongoing collaboration and dialogue with participants and other stakeholders the project proposed recommendations for policy and teacher education. This paper presents these recommendations and the research on which they were based. Throughout the study, mixed methods were employed, combining quantitative approaches used in surveys of policy and teachers' views based on a list of factors, alongside qualitative approaches employed in case studies of classroom practice. A strong conceptual framework developed at the start of the project guided data collection and analysis, as well as the presentation of findings and the development of policy recommendations, thus ensuring the latter's strong and consistent relationship with the relevant theoretical knowledge, the comparative research, analysis of classroom practices and the production of guidelines for teacher education.